Significance of the Capacity Recovery Effect in Pouch Lithium-Sulfur Battery Cells. (6th December 2016) - Knap, Vaclav; Zhang, Teng; Stroe, Daniel Ioan; Schaltz, Erik; Teodorescu, Remus; Propp, Karsten
Abstract : Lithium-Sulfur (Li-S) batteries are an emerging energy storage technology, which is technically-attractive due to its high theoretical limits; practically, it is expected that Li-S batteries will result into lighter energy storage devices with higher capacities than traditional Lithium-ion batteries. One of the actual disadvantages for this technology is the highly pronounced rate capacity effect, which reduces the available capacity to be discharged when high currents are used. This drawback might be addressed by the use of the capacity recovery effect, which by introducing relaxation periods between consecutive pulse discharges of the battery, increases the available discharge capacity of the cell. The capacity recovery effect of the Li-S cell is studied in this paper using the pulse discharge technique, considering its dependence on the applied current, discharge step length, temperature, and on the length of the relaxation period between the discharging pulses.